Communication that values patient autonomy is associated with satisfaction with care: a systematic review - Oliveira, Vinicius C.; Refshauge, Kathryn M.; Ferreira, Manuela L.; Pinto, Rafael Z.; Beckenkamp, Paula R.; Negrao Filho, Ruben F. [UNESP]; Ferreira, Paulo H. (Australian Physiotherapy Assoc, 2012)
Question: Which communication factors used by clinicians during patient-clinician interactions are associated with satisfaction with care? Design: Systematic review with meta-analysis of studies investigating the association of verbal or nonverbal factors or interaction styles used by clinicians with patient satisfaction during an encounter between clinician and patient. Participants: Clinicians interacting with patients in primary care or rehabilitation settings. Results: Twenty-seven studies investigated 129 verbal, nonverbal, and interaction style factors. of these, 38 factors were consistently associated with satisfaction. Verbal factors concerning clinicians involving, facilitating, and supporting patients were associated with satisfaction with care. Most communication factors presented a fair correlation (r >= 0.21 but < 0.41) with satisfaction with care. Nonverbal factors such as time spent discussing prevention and time spent reading patient charts had a fair association with satisfaction with care (correlations range from 0.21 to 0.40). A moderate association was found between interaction styles such as caring (pooled r = 0.51, 95% CI 0.42 to 0.60) and satisfaction with care. Over half (58%) of the 129 identified factors never associated with satisfaction with care and the remainder associated inconsistently. Conclusion: The number of potential modifiable communication factors associated with satisfaction with care and the magnitude of their association partially support interventions to train clinicians in communication skills that value patient autonomy. [Oliveira VC, Refshauge KM, Ferreira ML, Pinto RZ, Beckenkamp PR, Negrao Filho RF, Ferreira PH (2012) Communication that values patient autonomy is associated with satisfaction with care: a systematic review. Journal of Physiotherapy 58: 215-229]
Keywords: Communication; Systematic review; Professional-patient relations; Patient satisfaction